Characteristics and attributes of Oxisols under different land uses in the western region of the state of Bahia, Brazil - Fontana, Ademir; Teixeira, Wenceslau Geraldes; Balieiro, Fabiano de Carvalho; Moura, Thayane Pires Alves de; Menezes, Andressa Rosas de; Santana, Camila Ignez (Pesquisa Agropecuaria Brasileira, 2016)
The objective of this work was to evaluate the effects of different land uses on the characteristics and attributes of Oxisols in the western region of the state of Bahia, Brazil. The Oxisols had textures with largely predominant sand fraction, and they were evaluated in areas of cerrado, cotton, soybean, and common bean in the municipality of Luís Eduardo Magalhães. The morphological characterization and the collection of samples for evaluating soil physical and chemical attributes of horizons were carried out in small trenches, while the evaluation of field saturated hydraulic conductivity was done using the Guelph permeameter at two depths: 0.0 to 0.20 and 0.20 to 0.40 m. The evaluated Oxisols, besides their massive structure, showed a dense genetic horizon, which, under agricultural use, becomes more compacted, thick, and shallow, forming clods when plowed. Agricultural use reduces the saturated hydraulic conductivity of the evaluated Oxisols in both layers, except for common bean cultivation.